A Rare Case of Pancreatic Endometriosis Masquerading as Pancreatic Mucinous Neoplasm - Barton Huang; Annie Mooser; Danielle Carpenter; Grace Montenegro; Carrie Luu (Case Reports in Surgery)
Endometriosis is a relatively common condition among women, and pancreatic endometriosis has been reported on rare occasions. Such pancreatic lesions are difficult to diagnose and distinguish from other cystic lesions of the pancreas preoperatively. This report describes a case of pancreatic endometriosis in a 51-year-old female patient. Imaging demonstrated an enlarging cyst with findings concerning for a mucinous neoplasm. The patient underwent robotic distal pancreatectomy and splenectomy. Histopathology revealed an endometriotic cyst. Pancreatic endometriosis can be difficult to distinguish from other lesions of the pancreas. Surgical resection should be undertaken in cases where malignancy is suspected.